Strategy To Improve The Quality Of Human Resources Through Ziswaf Funds: Case Study Of The Smart West Pasaman Program - Urrahman, Assyfa; Aslami, Nuri; Silalahi, Purnama Ramadani (Amkop Management Accounting Review (AMAR), 2025)
Improving the quality of Human Resources (HR) through the utilization of Zakat, Infak, Sedekah, and Waqf (ZISWAF) funds is the primary strategy in supporting education for underprivileged communities in West Pasaman Regency. This study aims to analyze the plan for improving the quality of HR through the utilization of ZISWAF funds in the Smart West Pasaman program managed by BAZNAS. The method employed is a descriptive qualitative approach, utilizing data collection techniques that include interviews, observations, and documentation. The data analysis technique uses a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats that impact the program's success. The results of the study show an IFAS value of 3.06865 and an EFAS value of 2.98861, which places the program in quadrant I on the Cartesian diagram with an aggressive strategy (SO). This strategy leverages internal strengths to capitalize on external opportunities, such as government regulatory support and high demand for education. The implications of this study suggest that the strategic utilization of ZISWAF funds can expand the scope of beneficiaries, enhance program effectiveness, and contribute sustainably to improving the quality of human resources in West Pasaman Regency.